Writing Differently as A Contemporary Concept of Presenting Research Results in Management Sciences. Literature Review Announcement - Patrycja MIZERA-PĘCZEK (Communications of International Proceedings, 2023)
The article aims to present the conclusions from a review of the literature on writing differently in the area of ​​management sciences. Writing differently is the concept of creating scientific texts in an academic environment contrary to the established academic tradition. Methodologists and researchers note that both the proposed structure and the dominant language used in scientific articles impose a specific way of thinking about research problems undertaken in business schools. Moreover, they point out that the norms of academic writing require researchers to become somewhat of a blank slate, soulless and emotionless. Meanwhile, they suggest that the originality and value of the research problems being solved can be improved by communicating scientific content within the full context of the research experiences of the text's author. This short article reflects on the analysis of texts in which researchers declared that they were moving towards the trend of writing differently. The objectives of the articles and research problems undertaken by selected representatives of this trend in management sciences are presented.
Keywords: writing differently; academic writing; management sciences; methodology; humanistic trend; critical trend; SCOPUS database analysis